Pastoral Konseling bagi Kesehatan Mental Terhadap Remaja dan Pemuda pada Umur 15-23 Tahun - Immanuela J. Mumek (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2024)
The purpose of this study is to understand in depth and provide a clear picture of the factors that influence the emergence of excessive desire for mental health, as well as strategies in the context of pastoral counseling science to deal with problems for Adolescents and Youth aged 15-23 years. By using a descriptive case study approach, researchers can collect detailed and in-depth data from selected cases, thereby gaining a rich understanding of the factors that influence the emergence of excessive mental health or mental disorders and effective pastoral counseling strategies in dealing with these problems. Single case studies also allow researchers to study cases individually, exploring their backgrounds, experiences, and specific contexts. By integrating pastoral with a reality counseling approach, counselors can provide a comprehensive and effective approach in helping individuals achieve their goals. This approach considers the physical, psychological, social, and spiritual aspects of an individual's life, and helps individuals face and cope with the reality of their lives better.